Character Education in The Era of Sustainability: Strategies for Building Ethical and Resilient Generations - Mohammad Irsyad Wira Saputra; Zeinal Abidin; St. Maizah (re-JIEM (Research Journal of Islamic Education Management), 2026)
The accelerating pace of global change has made character education a critical foundation for achieving sustainable human development. This study explores strategies to strengthen character education within the framework of sustainability, emphasizing its role in nurturing ethical and resilient generations capable of addressing contemporary environmental, social, and moral challenges. Using a qualitative descriptive approach based on recent empirical and conceptual literature, this research identifies that character education aligned with sustainability principles fosters not only moral integrity but also environmental responsibility and socio emotional resilience. The study reviews prior research that examined character education through project-based learning, local wisdom, and digital literacy integration, while highlighting a significant gap in linking ethical formation and sustainability competencies. Findings suggest that integrated, contextual, and participatory approaches combining formal education, family engagement, and community collaboration are most effective in shaping sustainable character development. The research contributes to a theoretical framework and practical recommendations for policymakers and educators seeking to cultivate ethically grounded, socially responsible, and future-ready generations in an era of global uncertainty.